Elimination of H2S from chicken manure by reaction with H2O2 & titrating with KMnO4 - Muhamad Azhar, Azman (2010)
The process of odor removal from the chicken manure (H2S) can be done in several ways. One of them is the chemical reaction of chicken manure with H2O2 and titration with KMnO4. This research was done according to an improvised method with cautious handling of H2O2 and chicken manure. The research by using human smell detection used a scale of between 0 until 10 based on the odor strength; the value 0 for no odor and 10 for strangest chicken manure odor. For a volume of 1000mL chicken manure sample comprising 1 kg of improved sample with the addition of 500mL of 11ppm H2O2, it was found that there was no more odor of chicken manure and takes 3 hours for reaction between chicken manure and H2O2 to get 0 odor of chicken manure. Stiochometric calculation showed that when zero odors were reached in the first experiment 0.0001618 mol H2O2 would have reacted with 0.0001618 mol H2S. Actually by using the human smell detection the results at zero odors may not unrespond with complete removal with H2S because of the limits of sensitivity of the human nose. That means there may still exits some balance of H2S in chicken manure after reaction with H2O2 by using human detection to zero odors. So, the solution for this problem was using titration with KMnO4 for the balance of H2S in chicken manure to get to true zero odors or complete removal of H2S. The detector of H2S for this titration was the changing color of KMnO4 from dark purple to light pink. That means not changing color of KMnO4 indicates that the odor (H2S) was fully removed. The result obtained from the second experiment is 0.000451 mol KMnO4 react with 0.0003383 mol H2S. In calculations one tone of chicken manure contains 17.05g of H2S. In this research the pH value of the sample was maintained at near neutral condition of pH 7.28.